2014
DOI: 10.1080/15374416.2014.881292
|View full text |Cite
|
Sign up to set email alerts
|

Risk, Vulnerability, and Protective Processes of Parental Expressed Emotion for Children's Peer Relationships in Contexts of Parental Violence

Abstract: Objective This study examined risk, vulnerability, and protective processes of parental expressed emotion for children's peer relationships in families living in emergency shelters with high rates of exposure to parental violence (EPV). Parental criticism and negativity were hypothesized to exacerbate the association between EPV and poorer peer relations, while parental warmth was expected to buffer this association. Method Participants included 138 homeless parents (M = 30.77 years, SD = 6.33, range = 20.51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 66 publications
(139 reference statements)
3
29
0
Order By: Relevance
“…Economically disadvantaged families often show higher rates of marital problems, parental conflict, and domestic violence (Conger et al, 2010); such factors could mediate the relationship between educational level of the parent and peer relationship problems. Narayan, Sapienza, Monn, Lingras, and Masten (2015), in a sample of homeless, impoverished families, confirmed that domestic violence was related to peer relationship problems, mediated by the extent of parental warmth and of parental criticism and negativity.…”
Section: Discussionmentioning
confidence: 61%
“…Economically disadvantaged families often show higher rates of marital problems, parental conflict, and domestic violence (Conger et al, 2010); such factors could mediate the relationship between educational level of the parent and peer relationship problems. Narayan, Sapienza, Monn, Lingras, and Masten (2015), in a sample of homeless, impoverished families, confirmed that domestic violence was related to peer relationship problems, mediated by the extent of parental warmth and of parental criticism and negativity.…”
Section: Discussionmentioning
confidence: 61%
“…This study extends the use of the FMSS as a brief, effective tool in disadvantaged, impoverished and ethnically-diverse families (Narayan et al, 2012, 2014, Sher-Censor et al, 2013) to families where maltreatment and separation/divorce also are present in addition to poverty. Future studies should continue to make use of this efficient approach in samples where participants may have limited time to participate in lengthy measures of parent-child or family functioning.…”
Section: Discussionmentioning
confidence: 78%
“…Environments with maltreatment, separation/divorce, or both co-occurring circumstances in addition to EE-Crit would reflect an accumulation of family risk (Cicchetti & Lynch, 1993; Sameroff, Guttman, & Peck, 2003). Although EE-Crit has been extensively studied in clinically-referred, low-income, culturally diverse families (Frye & Garber, 2005; McCarty & Weisz, 2002; Peris & Hinshaw, 2003), some recent studies on EE have indicated that the predictive effects of EE-Crit may be less clear and potentially, more complex in families with very high cumulative risk (Narayan et al, 2012; Narayan, Sapienza, Monn, Lingras, & Masten, 2014). More research is needed to understand the associations between EE-Crit and family and child functioning in home environments with high cumulative risk.…”
mentioning
confidence: 99%
See 2 more Smart Citations